2009
DOI: 10.1007/s10450-009-9154-0
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of ethylene and ethane within single-walled carbon nanotubes. 1-Adsorption and equilibrium properties

Abstract: Endohedral adsorption properties of ethylene and ethane onto single-walled carbon nanotubes were investigated using a united atom (2CLJQ) and a fully atomistic (AA-OPLS) force fields, by Grand Canonical Monte Carlo and Molecular Dynamics techniques. Pure fluids were studied at room temperature, T = 300 K, and in the pressure ranges 4 × 10 −4 < p < 47.1 bar (C 2 H 4 ) and 4 × 10 −4 < p < 37.9 bar (C 2 H 6 ). In the low pressure region, isotherms differ quantitatively depending on the intermolecular potential us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 69 publications
1
20
0
Order By: Relevance
“…In the previous paper of this series (Cruz and Müller 2008) we showed that a fine description of the fluid molecules, in terms of a fully atomistic intermolecular potential model, as opposed to a simpler coarse-grained unitedatom model, captured some effects which otherwise would be lost when describing the adsorption on nanotubes. In Fig.…”
Section: Confined Fluidsmentioning
confidence: 97%
See 4 more Smart Citations
“…In the previous paper of this series (Cruz and Müller 2008) we showed that a fine description of the fluid molecules, in terms of a fully atomistic intermolecular potential model, as opposed to a simpler coarse-grained unitedatom model, captured some effects which otherwise would be lost when describing the adsorption on nanotubes. In Fig.…”
Section: Confined Fluidsmentioning
confidence: 97%
“…4). One needs to keep in mind that the highest density systems correspond to a nanopore which is totally filled, as determined in part I (Cruz and Müller 2008). Generally speaking, the MSD curves of Fig.…”
Section: Confined Fluidsmentioning
confidence: 99%
See 3 more Smart Citations